Evaluasi Degradasi NDF, ADF, dan NDIN dari Partikel Pakan Jerami Jagung dan Pucuk Tebu Dalam Rumen - Yunasri Usman (Agricultural Faculty, 2001)
ABSTRACT.Experiment were conducted to evaluate fermentation characteristics (pH, NH3, VFA), On degration in sacco degration neutral detergent fiber (NDF), acid detergent fiber (ADF) and neutral detergent insoluble nitrogen (NDIN) of feed particle in the rumen. Two fistulated Friesien Holstein grade of each feeding used in this research. The ration in given similar with the sample to measured the degration in the rumen are corn stover (CST) and sugar cane top (SCT). Disappearance of the NDF, ADF, and NDIN in the rumen was calculated based on the incubation time and using an exponential negative modwl Y= a + b (1-e-ct) from Orskov and Mc Donald, (1979). Values of a,b and c fraction were used to calculate theoretical degradation DT=a+ ((b.c)/(c+Kp)) with the assumption of flow of particle (Kp) is about 5 %/hour. The results on fermentation characteristics of feeding corn stover give ph about 6.54 0.16; N-NH3 about 7.36 3.10 mg/100 ml and VFA about 64.84 10.82 mmol/1, whilst for feeding sugar can to give ph about 6.54 0.14; NH3 about 2.62 0.85 mg/100 ml and VFA about 44.13 6.7 mmol/1. The microbe activity of the degration (DT) borh fed were not significantly different for NDF and ADF but for NDIN showed significantly different (P0.05) among feeds. This results show that there utilization of single feeds corn stover and sugar can top are not optimal for microbe activity, however the values degradation of fiber fraction were above 30%.